2006
DOI: 10.1537/ase.041228
|View full text |Cite
|
Sign up to set email alerts
|

Kinship analysis of the Jomon skeletons unearthed from a double burial at the Usu-Moshiri site, Hokkaido, Japan

Abstract: Kinship analysis was performed on a Jomon double burial from the Usu-Moshiri site in Hokkaido, Japan, using odontometric data in conjunction with mitochondrial DNA data. Q-mode correlations with respect to tooth crown measurements indicated a low similarity between the two adult female skeletons found from this burial. Moreover, mitochondrial DNA analysis revealed that these individuals were not maternal relatives. Consequently, judging from both morphological and genetic evidence, these skeletons are more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
(18 reference statements)
0
20
0
Order By: Relevance
“…In addition, DNA extracts from 4 Usu-Moshiri (Adachi et al, 2003(Adachi et al, , 2006) and 14 Funadomari (Adachi et al, 2009) individuals, which were previously subjected to mtDNA analysis, were used for further analyses in this study (see Fig. 1).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…In addition, DNA extracts from 4 Usu-Moshiri (Adachi et al, 2003(Adachi et al, , 2006) and 14 Funadomari (Adachi et al, 2009) individuals, which were previously subjected to mtDNA analysis, were used for further analyses in this study (see Fig. 1).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…36,37,[40][41][42]52 Primer MT1 corresponds to the HVI segment (nucleotide position (n.p.) 16185À16439 of the revised Cambridge Reference Sequence (rCRS)) ( Table 2).…”
Section: Dna Amplificationmentioning
confidence: 99%
“…Using molecular biological methods, Adachi et al 40,42 reported kinship analysis for skeletal specimens found in double burials excavated from the Jomon site. However, as there are many different factors, such as period, geographical region and burial style, between their study and our study, it is difficult to compare the results.…”
Section: Cases Of Vicinal Burialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been applied several times to Jomon populations (Kondo, 1994;Matsumura and Nishimoto, 1996) and has also been cross-checked against ancient DNA data (Shinoda et al, 1998;Adachi et al, 2003Adachi et al, , 2006. Although the exact nature of genealogical relationships among individuals can be rarely specified without a priori knowledge, biodistance analysis can reveal relative relatedness among them (Stojanowski and Schillaci, 2006).…”
Section: Introductionmentioning
confidence: 99%